Springer Series in Light Scattering Volume 2: Light Scattering, Radiative Transfer and Remote Sensing (Springer Series in Light Scattering,, 2018)
This book presents a survey of modern theoretical and experimental techniques in studies of light scattering phenomena and radiative transfer processes in random media. It presents reviews on light scattering by sea water and bubbles, and includes a separate chapter addressing studies of the remote sensing of crystalline clouds with a focus on the shape of particles-a parameter rarely studied by passive remote sensing techniques. In particular, it offers a comprehensive analysis of polarized radiative transfer in optically active (e.g., chiral) light scattering media and explores advances in spectro-polarimetry of particulate media. Lastly it discusses new developments in light scattering for combustion monitoring.